PREOPERATIVE AND INTRAOPERATIVE RISKS OF ERRORS IN CYSTS SURGERY OF THE BILE DUCTS IN CHILDREN - E. A. Yakubov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study analyzed preoperative errors and intraoperative risks in cystic transformations of the bile duct in children. MATERIALS AND METHODS. The data of 76 patients with cystic transformations of the bile duct were evaluated. Various operations were performed on 74 (97,4 %) patients. RESULTS. There were noted different complications in 34 cases on the stage of diagnostics and surgical treatment. The iatrogenic complications were observed in patients with complex anatomical and topographic anomalies. The article presents the most frequent complications, their causes and features of treatment approach. CONCLUSIONS. Diagnostic and tactical errors were made due to low awareness of doctors regarding cystic transformations of the bile duct and lack of clear symptoms of dynamic characteristics of clinical signs of the defect. Risk of intraoperative complications would be increased because of earlier performed an erroneous or inadequate surgery and expressed inflammatory process of hepatoduodenal area.